2002
DOI: 10.1002/bip.10230
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting viral proteases: Challenges and opportunities

Abstract: Inhibitor design against viral targets must take into account the peculiar characteristics of viral biology-in particular, the plasticity of their replicative machinery. This includes maturational cleavage of the polyprotein, which is mediated by virally encoded proteases. Designing against a movable target is particularly challenging, but at the same time it offers new opportunities. Here we describe our experience with the NS3/4A (NS: nonstructural) serine protease of human hepatitis C virus (HCV). By extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…After extensive dialysis, wild-type NS2B(H)-NS3pro exhibited complete autoproteolytic cleavage, which resulted in two protein products of 20 kDa and 10 kDa, whereas the S135A mutant was completely inactive in the self-cleavage assay. In Western blot analysis, only the 10-kDa protein reacted with anti-Xpress antibodies directed against the polyhistidine tag, which confirmed that this protein represents the N-terminal cleavage fragment (His) 6 …”
Section: Generation Of Mutants the Sequencementioning
confidence: 75%
See 2 more Smart Citations
“…After extensive dialysis, wild-type NS2B(H)-NS3pro exhibited complete autoproteolytic cleavage, which resulted in two protein products of 20 kDa and 10 kDa, whereas the S135A mutant was completely inactive in the self-cleavage assay. In Western blot analysis, only the 10-kDa protein reacted with anti-Xpress antibodies directed against the polyhistidine tag, which confirmed that this protein represents the N-terminal cleavage fragment (His) 6 …”
Section: Generation Of Mutants the Sequencementioning
confidence: 75%
“…Expression of the mutant derivatives as inclusion bodies in E. coli and purification under denaturing conditions by immobilized metal chelate chromatography and gel filtration yielded homogeneous products, as determined by SDS-PAGE analysis. The 29.8-kDa (His) 6 -NS2B(H)-NS3pro molecule displayed anomalous migration in gel electrophoresis with a higher apparent molecular mass of approximately 37 kDa. Subsequent refolding was performed by stepwise dialysis, and correct cleavage at the NS2B/NS3 junction was confirmed for the wild-type protein by N-terminal amino acid sequencing of the 20-kDa cleavage product, which yielded the sequence AGVLW, identical to the first five residues of the NS3 protein.…”
Section: Generation Of Mutants the Sequencementioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between the NS3 protease and its substrates is characterized by a series of weak contacts that extend over 10 amino acid residues, requires a cysteine in the P 1 position, and relies on high charge densities (17). Thus, substrate recognition by the NS3 protease is more reminiscent of the protein-protein interactions found in an enzyme-protein inhibitor pair than of a "conventional" enzyme-substrate complex (12,17).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…The interaction between the NS3 protease and its substrates is characterized by a series of weak contacts that extend over 10 amino acid residues, requires a cysteine in the P 1 position, and relies on high charge densities (17). Thus, substrate recognition by the NS3 protease is more reminiscent of the protein-protein interactions found in an enzyme-protein inhibitor pair than of a "conventional" enzyme-substrate complex (12,17).In this article, we hypothesized that the bioengineering of a naturally occurring serine protease inhibitor (serpin) scaffold could provide a new approach to developing high affinity, selective NS3 protease inhibitors (18,19). Serpins differ from…”
mentioning
confidence: 99%